Evaluation of in vitro macrophage differentiation during space flight - Ortega, M. Teresa; Lu, Nanyan; Chapes, Stephen K. (My University, 2012)
We differentiated mouse bone marrow cells in the presence of recombinant macrophage colony stimulating (rM-CSF) factor for 14 days during the flight of space shuttle Space Transportation System (STS)-126. We tested the hypothesis that the receptor expression for M-CSF, c-Fms was reduced. We used flow cytometry to assess molecules on cells that were preserved during flight to define the differentiation state of the developing bone marrow macrophages; including CD11b, CD31, CD44, Ly6C, Ly6G, F4/80, Mac2, c-Fos as well as c-Fms. In addition, RNA was preserved during the flight and was used to perform a gene microarray. We found that there were significant differences in the number of macrophages that developed in space compared to controls maintained on Earth. We found that there were significant changes in the distribution of cells that expressed CD11b, CD31, F4/80, Mac2, Ly6C and c-Fos. However, there were no changes in c-Fms expression and no consistent pattern of advanced or retarded differentiation during space flight. We also found a pattern of transcript levels that would be consistent with a relatively normal differentiation outcome but increased proliferation by the bone marrow macrophages that were assayed after 14 days of space flight. There also was a surprising pattern of space flight influence on genes of the coagulation pathway. These data confirm that a space flight can have an impact on the in vitro development of macrophages from mouse bone marrow cells.
Keywords: Gene expression; Differentiation; Macrophage colony stimulating factors; STS-126